2022
DOI: 10.3389/fcimb.2022.1050497
|View full text |Cite
|
Sign up to set email alerts
|

In silico high-throughput screening system for AKT1 activators with therapeutic applications in sepsis acute lung injury

Abstract: PurposeAKT1 is an important target in sepsis acute lung injury (SALI). The current study was aim to construct a high-throughput screening (HTS) system based on the ChemDiv database (https://www.chemdiv.com/complete-list/) and use the system to screen for AKT1 activation agents, which may provide clues for the research and development of new drugs to treat SALI.MethodsBased on the existing X-ray structure of AKT1 and known AKT activators, a large-scale virtual HTS was performed on the ChemDiv database of small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…However, adipose-derived mesenchymal stem cells-derived exosomes have been found to inhibit lung hemorrhage and edema, and reduce vascular hyper-permeability by activating the PI3K-AKT pathway and protecting endothelial cells ( 34 ). In a previous study, it was demonstrated that mTOR can directly bind to Bax in HUVECs, highlighting the importance of studying drugs that can interfere with the PI3K-AKT-mTOR pathway for the prevention and treatment of SALI ( 18 ). Therefore, it is very important to study and explore drugs that can interfere with the PI3K/AKT/mTOR pathway for the prevention and treatment of SALI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, adipose-derived mesenchymal stem cells-derived exosomes have been found to inhibit lung hemorrhage and edema, and reduce vascular hyper-permeability by activating the PI3K-AKT pathway and protecting endothelial cells ( 34 ). In a previous study, it was demonstrated that mTOR can directly bind to Bax in HUVECs, highlighting the importance of studying drugs that can interfere with the PI3K-AKT-mTOR pathway for the prevention and treatment of SALI ( 18 ). Therefore, it is very important to study and explore drugs that can interfere with the PI3K/AKT/mTOR pathway for the prevention and treatment of SALI.…”
Section: Discussionmentioning
confidence: 99%
“…The elution was carried out using 1X Laemmli buffer, and the Bax protein was analyzed by WB analysis from the elution content. The protocols for SDS-PAGE and WB have been previously described ( 18 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation